2022
DOI: 10.1021/acs.jpcb.2c01768
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of ATP on PHF6 Aggregation

Abstract: The aggregation of Tau protein, which are involved in Alzheimer’s disease, are associated with the self-assembly of the hexapeptide sequence, paired helical filament 6 (PHF6) from repeat 3 of Tau. In order to treat Alzheimer’s disease and other such tauopathies, one of the therapeutic strategies is to inhibit aggregation of Tau and its nucleating segments. Therefore, we have studied the effect of adenosine triphosphate (ATP) on the aggregation of PHF6. ATP has, interestingly, demonstrated its ability to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 135 publications
0
11
0
Order By: Relevance
“…The study of peptide–ligand interactions via MD simulations requires a lot of computational resources which are cost- and time-consuming. Hence, nowadays, biased simulation methods such as umbrella sampling methods, metadynamics, and steered MD are employed, so that the protein–ligand complex is able to sample the whole conformational ensemble. ,,,, In replica exchange MD, exchange of conformations trapped at different temperatures occurs, which also improves sampling of systems. , Discrete MD has become popular to investigate amyloid peptides and is computationally more efficient than conventional MD. In order to compute larger systems and access wider time scales, coarse-grain simulations are also used.…”
Section: Methods To Determine the Anti-amyloid Properties Of Small Mo...mentioning
confidence: 99%
See 2 more Smart Citations
“…The study of peptide–ligand interactions via MD simulations requires a lot of computational resources which are cost- and time-consuming. Hence, nowadays, biased simulation methods such as umbrella sampling methods, metadynamics, and steered MD are employed, so that the protein–ligand complex is able to sample the whole conformational ensemble. ,,,, In replica exchange MD, exchange of conformations trapped at different temperatures occurs, which also improves sampling of systems. , Discrete MD has become popular to investigate amyloid peptides and is computationally more efficient than conventional MD. In order to compute larger systems and access wider time scales, coarse-grain simulations are also used.…”
Section: Methods To Determine the Anti-amyloid Properties Of Small Mo...mentioning
confidence: 99%
“…The inhibitory capacity of artemisin is more pronounced toward hIAPP than toward Aβ aggregation . Adenosine triphosphate (ATP) not only prevents the oligomerization of the amyloid-prone Aβ 16–22 and tau 306‑311 monomers but also converts Aβ 42 oligomers into off-pathway species. , In addition, ATP preferentially interacts with the terminal residues of hIAPP to prevent its oligomerization . The adenosine moiety of ATP interacts with the charged and hydrophobic peptide residues and hence contributes more than the hydrophilic triphosphate group toward peptide-ATP binding.…”
Section: Anti-amyloid Activity Of Other Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The small peptide-based inhibitors used in our study were constructed by AMBERTools (Figure b). The isomers of aminobenzoic acid inserted in the peptides were parameterized using pyRED calculations on the R.E.D server. The AMBER14SB force field was utilized for modeling the peptides, following previous studies. Studies by Man et al revealed that the AMBER14SB force field is suitable for amyloid simulations since the protein–protein and protein–solvent interactions are well balanced in this force field. , It also provides a good balance in the structure and kinetics of amyloid formation . Four hIAPP monomers were placed sufficiently apart in a cubic box such that the hIAPP monomers are at least 20 Å apart.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The formation of a hydrogen bond between a donor (D)–acceptor (A) pair was considered if the D–A distance was within 3.5 Å and the D–A–H angle is within 45°. , The clustering was carried out using the density-based spatial clustering of applications with noise (DBSCAN) clustering algorithm. , An isovalue of 0.5 was considered for evaluating the spatial distribution functions of the inhibitor peptides around hIAPP . The first solvation shell coordination number of the BSBHps was determined by the number of the respective BSBHps present within a distance of 5 Å from each residue of hIAPP, considering all of the heavy atoms, , while a nonpolar contact between hIAPP and BSBHps was defined by the same, considering only the aliphatic carbon atoms. , π–π stacking was considered when the distance between two aromatic rings was within 6.5 Å, and the angle (formed by the normals of two aromatic rings of two interacting species) was in the range of 0–30° or 150–180° for parallel stacking, 30–60° or 120–150° for a herringbone orientation, and 60–120° for perpendicular or T-shaped stacking …”
Section: Simulation Methodsmentioning
confidence: 99%